AS INFLUÊNCIAS DA GLOBALIZAÇÃO E DO ECONOMICISMO NA IDENTIDADE CULTURAL INDIANA - RODRIGUES, BRUNA RAFAELLA MATOS (Portal de Trabalhos Acadêmicos, 2019)
The Globalization appears as the phenomenon responsible for great changes in the world mainly from the 1990 decade. After the Cold War‟s end, the neo-liberal ideology and capitalism could propagate it‟s ideals for most countries by deepening and strengthening of global relations through technological and telecommunications innovations. Capitalist pursuit of economic growth gave rise to economism, a contemporary phenomenon that is the consequence of state‟s reduction of all other social spheres on behalf of economy. The economism brings with it the needing of adaptation to global standards, as a result there is absorption of the cultural values of hegemonies. The adaptation to the global standards is causing major changes in culture and cultural identity in many countries, as is the case in India, a country of ancient cultural traditions, which had its economic liberalization in 1990 and since then has suffering changes in their traditions and customs. The permeability of Western values in India can result in changes in the Indian cultural identity and in every society, thus providing the appearance of a homogeneous culture, a world culture.